Cation Diffusion Guides Hybrid Halide Perovskite Crystallization during the Gel Stage. (11th February 2020) - Liu, Lang; Bai, Yang; Zhang, Xiao; Shang, Yuequn; Wang, Chenyue; Wang, Hao; Zhu, Cheng; Hu, Chen; Wu, Jiafeng; Zhou, Huanping; Li, Yujing; Yang, Shihe; et al.
Abstract: Lead halide perovskites with mixed cations/anions often suffer from phase segregation, which is detrimental to device efficiency and their long‐term stability. During perovskite film growth, the gel stage (in between liquid and crystalline) correlates to phase segregation, which has been rarely explored. Herein, cation diffusion kinetics are systematically investigated at the gel stage to develop a diffusion model obeying Fick's second law. Taking 2D layered perovskite as an example, theoretical and experimental results reveal the impact of diffusion coefficient, temperature, and gel duration on the film growth and phase formation. A homogenous 2D perovskite thin film was then fabricated without significant phase segregation. This in‐depth understanding of gel stage and relevant cation diffusion kinetics would further guide the design and processing of halide perovskites with mixed composition to meet requirements for optoelectronic applications. Abstract : Gemischte Bleihalogenid‐Perowskite sind oftmals durch Phasentrennung charakterisiert, welche mit der Diffusionskinetik der Kationen im Gelstadium zusammenhängt. Nun wurde erfolgreich ein homogener dünner 2D‐Perowskitfilm ohne signifikante Phasentrennung hergestellt. Die Ergebnisse sollten das Design und die Herstellung von Halogenidperowskiten für optoelektronische Anwendungen vereinfachen.